2006
DOI: 10.1063/1.2198088
|View full text |Cite
|
Sign up to set email alerts
|

Relaxor ferroelectricity in strained epitaxial SrTiO3 thin films on DyScO3 substrates

Abstract: Effect of stoichiometry on the dielectric properties and soft mode behavior of strained epitaxial SrTiO3 thin films on DyScO3 substrates Appl. Phys. Lett. 102, 082905 (2013); 10.1063/1.4793649 The effect of the top electrode interface on the hysteretic behavior of epitaxial ferroelectric Pb(Zr,Ti)O3 thin films with bottom SrRuO3 electrode J. Appl. Phys. 112, 064116 (2012); 10.1063/1.4754318 Dielectric and ferroelectric properties of strain-relieved epitaxial lead-free KNN-LT-LS ferroelectric thin films on Sr T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
78
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 37 publications
6
78
1
Order By: Relevance
“…The relaxorlike properties evidenced in epitaxial films of ðBa; SrÞTiO 3 [13] indicate a presence of the short-range-order region in the phase diagram for this FE, too. Similar short-range order found in epitaxial films grown by different methods and in different laboratories [9,12,13] suggests its fundamental origin, not related to technological imperfections. Studies of dynamic effects might give a clue to understanding this origin [12,28].…”
Section: -2mentioning
confidence: 60%
See 3 more Smart Citations
“…The relaxorlike properties evidenced in epitaxial films of ðBa; SrÞTiO 3 [13] indicate a presence of the short-range-order region in the phase diagram for this FE, too. Similar short-range order found in epitaxial films grown by different methods and in different laboratories [9,12,13] suggests its fundamental origin, not related to technological imperfections. Studies of dynamic effects might give a clue to understanding this origin [12,28].…”
Section: -2mentioning
confidence: 60%
“…1). This differs from the relaxorlike state in epitaxial films of quantum paraelectric SrTiO 3 with the in-plane tensile strain s % 1% [9], also well beyond the theoretical paraelectric gap [4,5]. To demonstrate that strain-induced FE order is characteristic not only for KTO or compressive strain, we show here the temperature dependence of refraction index nðTÞ measured in epitaxial film of SrTiO 3 with the in-plane tensile strain s ¼ 2:1%.…”
Section: -2mentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, strain-induced ferroelectricity of SrTiO 3 thin films was reported mainly along the inplane direction. 21,22,42 Very few reports describe phenomena along the out-of-plane direction. [43][44][45] The out-of-plane ferroelectricity reported by Warusawithana et al 43 is limited in terms of thickness (less than 10 ML) and that reported by Kim et al 44,45 originates from vacancies.…”
Section: Resultsmentioning
confidence: 99%